Analysis Planning Upper Structure Bridge: A Case Barelang-2 Bridge, Batam - Dwiyana Firayanti; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2023)
A bridge is part of a highway or city road, which is part of a city or community development plan. Therefore, the function of a bridge is not determined by the bridge expert. The definition of a successful bridge or structure is safe, functional, affordable, and beautiful. The purpose of bridge planning in Barelang is to connect the road from the Batam road area, and towards the Galang road area to produce more efficient, and effective traffic. The purpose of bridge planning is to find out how the structural calculation of the strength of the planned bridge is a means of connecting the road area to other road areas and reducing traffic congestion on the road. This method is a direct review of the location to be studied with the aim of knowing the existing conditions at the location, and documenting all conditions at the research location, reviewing previous journals with similar research, as an overview of the author's calculations, and analysis in conducting the research to be planned. Based on calculations on the planning of the upper bridge structure, the loading value on the dead load is 0.88307 t / m, and the live load is 18.518 t/m. The author also performs planning calculations in vehicle floor mechanics where the dead load is obtained at 0.41535 t/m, and live load 6.4581 t/m. For implementation using reinforcement must be by the plan so that it becomes an efficient bridge and does not experience a lack of strength in the structure.